New Testament criticism and interpretation essays on methods and issues - Black, David Alan, 1952-; Dockery, David S. (Grand Rapids, MI Zondervan, 1991)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. -- hermeneutics; Bible. N.T. -- criticism, interpretation, etc